Post traumatic cutaneous mucormycosis: a diagnostic dilemma - Nair, Kharishma P.; S., Siddartha Gowthaman; Bagalgotkar, Meghana S.; S., Vinoth; Manickam, Ramanathan (International Surgery Journal, 2021)
The incidence of mucormycosis, an invasive fungal disease, is more in the developing countries, especially among the immunocompromised individuals. However, this disease can also occur in those without any predisposing factors. In the developed countries, those undergoing haematopoetic stem cell transplantation were more prone to developing this disease. There can be varied presentations of mucormycosis. It could be rhinocerebral, pulmonary, cutaneous, gastrointestinal or even disseminated forms. Post traumatic mucormycosis is infrequently reported and is often difficult to diagnose earlier due to its unusual presentation. In this case report, we describe two patients who acquired cutaneous mucormycosis following traumatic wounds and how they characteristically presented with 3 zones which was identified by us and has not been reported of earlier. This can help in diagnosis of this condition earlier and to follow the treatment protocol accordingly and prevent the morbidity and mortality associated with this disease.